PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA BANK DANAMON UNIT BETUNG - Ridwan, Muhammad (JURNAL KOMPETITIF, 2013)
ABSTRACTÃ‚Â This study discusses the effect of Service Quality Of Customer Loyalty In Bank Danamon Betung Unit, where one of the elements to improve customer loyalty at Bank Danamon Unit Betung one of which is the quality of service. The research was carried out in 5 months, where the research was conducted in Bank Danamon Betung Unit located at Jalan Rimba Palembang Jambi Sub Sub Acid Betung Banyuasin regency in South Sumatra province. In this study researchers determined the population of 500 existing customers in Bank Danamon Betung Unit. The authors took a sample of 10% of 50 customers of Bank Danamon Betung Unit.From these results obtained influence of service quality on customer loyalty at Bank Danamon Betung Unit. Where the results of calculations performed with SPSS version 15 as follows: there is the influence of service quality on customer loyalty at Bank Danamon Betung Unit. Linear regression equation Y = 12.043 + 0.713 X. Of the correlation coefficient r = 0.685 or 68.5%, meaning that the relationship between the variables of service quality is quite tight and the direction (positive correlation) of 68.5% with variable customer loyalty. The coefficient of determination (R2) of 0.47 or 47%, the value can be interpreted for the percentage of influence of variables of service quality on customer loyalty at Bank Danamon Betung Unit. While the remaining 53% is influenced by other factors.Ã‚Â Key Word : Influence, Quality, Service, Loyalty.Ã‚Â